Recycled coarse aggregates from pelletized unused concrete for a more sustainable concrete production. (10th May 2019) - Bassani, M.; Diaz Garcia, J.C.; Meloni, F.; Volpatti, G.; Zampini, D.
Abstract: A significant amount of the concrete produced worldwide is returned unused to production plants and has the potential to cause serious damage to natural soils and waters. This study proposes the use of a new pelletization process to convert fresh unused concrete into an artificial aggregate, which can be reintroduced into the concrete production cycle. Specifically, the investigation focuses on the properties of two pelletized recycled aggregates (PRAs) derived from two sources of an unsettled cementitious mixture. This research is based on the hypothesis that properties of the returned concrete may affect the characteristics of PRAs. PRAs were evaluated by particle size distribution, particle density, water absorption, resistance to fragmentation, and chemical and mineralogical analysis. Test results confirm that the concrete influences some properties of PRAs, and that PRAs exhibit different properties to those of conventional aggregate. However, it can be reused in place of natural coarse aggregate in the production of new concrete. Highlights: Unused fresh concrete constitutes an environmental impact issue for the Concrete Industry. Pelletization is a way to convert unsettled concrete into a new aggregate. Characterization of pelletized recycled aggregate (PRA) from two different concretes. Properties of original concrete are partially transferred to PRA. PRA can be reintroduced into the concrete production process as an alternative aggregate source.